Kepemimpinan Kewirausahaan di Bidang Pendidikan - Dian Rosinawati; Syaefullo Syaefullo; Azi Khoirurrahman (Universitas Islam Bunga Bangsa Cirebon, 2021)
The application of entrepreneurship in educational institutions by school principals can be through the management of programs that can grow and develop their schools in producing real work that is highly competitive in order to prepare the future of their students in the midst of the complex challenges of entering Industry 4.0. This study aims to determine the spirit of entrepreneurship in education leadership based on religion, philosophy, psychology and sociology. This research is a type of library research by collecting library data, taking notes and reading and processing research materials. The results of the study show that 1) Success in entrepreneurship will come to someone who carries out the teachings of Islam in their activities, and always tries and does not give up in running it. 2) The essence of entrepreneurship for educational leadership or school principals is not making him an entrepreneur but making him an agent of change for creative ideas, innovations, his findings, implementing competitive models, approaches, management and leadership strategies and producing quality for his educational institutions. 3) The ability that must be possessed by an educational leader in carrying out his role as an entrepreneur in an educational institution is to have an entrepreneurial spirit, attitude, and behavior. 4) The entrepreneurial influence of educational leadership in terms of the social environment, the creativity and innovation of an educational leader can realistically be utilized for the benefit of students, teachers and institutions as well as for the community using graduates who are competitive and useful in society. ABSTRAK Penerapan kewirausahaan pada Lembaga Pendidikan oleh kepala sekolah dapat melalui pengelolaan program-program yang dapat menumbuhkan dan mengembangkan sekolahnya dalam menghasilkan karya nyata yang berdaya saing tinggi guna mempersiapkan masa depan peserta didiknya di tengah kompleksitas tantangan memasuki Industri 4.0. Penelitian ini bertujuan untuk mengetahui jiwa enterpreneurship dalam kepemimpinan pendidikan berbasis agama, filsafat, psikologi dan sosiologi. Penelitian ini merupakan jenis riset kepustakaan (library research) dengan pengumpulan data pustaka, mencatat dan membaca serta mengolah bahan penelitian. Adapun hasil penelitian menunjukan bahwa 1) Keberhasilan dalam berwirausaha akan datang pada seseorang yang melaksanakan ajaran agama Islam pada kegiatannya, serta selalu berusaha dan tidak menyerah dalam menjalankannya. 2) Hakikat kewirausaan untuk kepemimpinan Pendidikan atau Kepala Sekolah bukanlah menjadikannya sebagai pengusaha tetapi menjadikannya seorang agen perubahan atas ide kreatifitas, inovasi-inovasi hasil temuannya implementasi model, pendekatan, strategi manajemen dan kemimpinan yang berdaya saing dan menghasilkan mutu bagi Lembaga pendidikannya. 3) Kemampuan yang harus dimiliki seorang kepemimpinan Pendidikan dalam menjalankan perannya sebagai seorang entrepreneur di Lembaga Pendidikan, yaitu memiliki memiliki jiwa, sikap, dan perilaku kewirausahaan. 4) Pengaruh kewirausahaan kepemimpinan Pendidikan ditinjau dari kacamata lingkungan sosial maka kreatifitas dan inovasi dari seorang pemimpin kependidikan secara realistik dapat dimanfaatkan untuk kepentingan peserta didik, guru-guru dan lembaganya serta bagi masyarakat pengguna lulusannya yang mempunyai daya saing dan berguna di masyarakat.